Perbandingan Pengaturan Kuota Pemilihan Perempuan dan Kondisi Keterwakilan Perempuan di Parlemen: Studi Kasus Indonesia, Timor-Leste, dan Finlandia (A Comparison Study of the Quotas and Conditions for Women's Representation in Parliament in Indonesia, Timor-Leste, and Finland) - Sibarani, Ramadhanya Elwinne Huzaima (The Indonesian Journal of Socio-Legal Studies, 2024)
Women’s representation in parliament is an important aspect of improving gender equality in a country. As of the 2019 parliamentary elections, women’s representation in the Parliament of the Republic of Indonesia (DPR RI) has only reached 21.4%. This figure is far below Timor-Leste and Finland, which respectively have 40% and 47% women’s representation. To increase the number of women’s representation in parliament, there is a concept called women's electoral quota. This study attempts to compare how women’s electoral quotas are regulated in Indonesia, Timor-Leste, and Finland. In addition, this study also reviews the condition of women’s representation in the parliaments of the three countries. Hanna F. Pitkin explains that there are 4 (four) types of representation, namely formal, descriptive, substantive and symbolic. This research focuses on descriptive representation because it relates to the quantity of women's representation in parliament, as well as substantive representation because this research also wants to formulate a strategy to maximize the quality of women's representation in parliament. The results of this study indicate that in terms of descriptive representation, Indonesia is lacking because the women’s electoral quota in the form of serial numbers does not work optimally; and women’s lack political participation, especially because political parties in Indonesia do not apply party quotas. Meanwhile, in terms of substantive representation, Timor-Leste and Finland are both superior due to ongoing communication with civil society and the strong role of the women’s parliamentary caucus. From there, several strategies were formulated in the context of increasing women’s representation in the DPR RI, namely increasing women’s political participation, reforming women’s election quotas in the form of serial numbers, opening large communication spaces between women parliamentarians and civil society, and strengthening the role of women’s parliamentary caucus in DPR RI. Keywords: women’s representation in parliament, women’s electoral quotas, and women’s political participation